Pengaruh Hubungan Pemasaran Terhadap Loyalitas Pelanggan PT Finansia Multi Finance/kredit plus Manado - Gerry Wido Kaolang; J. A.F. Kalangi; Roy Runtuwene (JURNAL ADMINISTRASI BISNIS, 2016)
Abstract.The purpose of this study was to determine the effect of the application of Relationship Marketing (Relationship Marketing) on Customer Loyalty in PT Finansia Multi Finansia / credits plus the Branch Office Manado. Correlation test is to determine the effect of relationship marketing on customer loyalty by comparing tcount for Employee Empowerment variable (X) is greater than t table and show that t is greater than t table so Ho rejected and Ha accepted.With this shows that there is a positive relationship between the application and direction Relationship Marketing and customer loyalty. Keywords: Relationship Marketing, Customer Loyalty